A comprehensive study of the effect of biochar on the rheological properties and durability of asphalt concrete mixtures - Krayushkina, Kateryna; Bondarchuk, Vadym; Stepanchuk, Oleksandr; Talavira, Hennadii (International Conference “Environmental Engineering”, 2026)
A comprehensive study of the effect of biochar on the rheological properties and durability of asphalt mixtures is particularly relevant given the need to improve the performance of road surfaces and implement environmentally friendly technologies. Biochar, obtained through the pyrolysis of plant materials, is considered a promising additive capable of improving the structural and mechanical properties of bitumen and mineral-bitumen composites. This study analyzed changes in the rheological parameters of bitumen binders at various biochar concentrations (from 2 to 10% by weight), including viscosity, complex shear modulus, and temperature sensitivity. It was found that the addition of bio-char improves the binder’s structural stability by improving particle size distribution and increasing the amount of high-molecular-weight fractions. The impact of biochar on the durability of asphalt concrete was also assessed in terms of water resistance, crack resistance, and rutting. Test results indicate a reduction in bitumen aging, increased fatigue resistance, and improved thermal stability of the composite. Optimum biochar concentrations ensure the formation of a denser structure, preventing moisture penetration and the development of microcracks. The comprehensive analysis demonstrates that the use of biochar as a modifying additive not only improves the performance characteristics of asphalt mixtures but also enhances the environmental sustainability of road construction through the use of renewable materials and reduced CO2 emissions. The results confirm the potential for further integration of biochar into asphalt concrete production processes.
Keywords: biochar; asphalt mixture; rheological parameters; modification